Response of Sweet Corn (Zea mays saccharata Sturt) to Different Decomposers and Rice Straw Compost Dosages - Jamilah jamilah (CV. HEI PUBLISHING INDONESIA, 2025)
This study was conducted in Kalumbuk Subdistrict, Kuranji District, Padang City, to evaluate the effects of decomposer type and rice straw compost dosage on the growth and yield of sweet corn. The objective of the study was to determine the effect of decomposer origin and rice straw compost dosage on the growth and yield of sweet corn. The experiment used a factorial randomized complete block design (RCBD) with two factors. The first factor was the type of decomposer consisting of three sources: natural (no added decomposer), EM4, and Crocober Plus LOF (CP LOF). The second factor was the rice straw compost dosage consisting of three levels: 10, 15, and 20 tons per hectare. The results showed no significant interaction between decomposer type and compost dosage on plant height and Leaf Area Index (LAI). However, both decomposer type and compost dosage had significant main effects. Crocober Plus (CP LOF) and EM4 liquid significantly improved plant growth and yield compared to natural decomposer, with CP LOF producing the best results. The optimal compost dosage was 15 t ha⁻¹, which resulted in a maximum yield of 27.46 t ha⁻¹ of fresh ear weight.